2005
DOI: 10.1007/bf03345339
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rosiglitazone and metformin on insulin resistance and serum androgen levels in obese and lean patients with polycystic ovary syndrome

Abstract: Our data showed that both metformin and rosiglitazone increased insulin sensitivity in obese patients with PCOS as expected, and in lean patients as well. Rosiglitazone seemed to be more effective in decreasing the androgen levels and in achieving slightly greater improvement in menstrual disturbance than metformin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 42 publications
1
48
1
1
Order By: Relevance
“…This drug also reduces appetite in many PCOS women and is thus often [133], but not always [134], associated with more weight loss. Metformin has been shown to be effective in all women with PCOS, even those without insulin resistance and hyperinsulinemia [47, [135][136][137], but tends to be more effective in lean as compared to obese PCOS women [138]. The effects of metformin in PCOS are probably mainly mediated through a reduction in insulin levels, which is observed both in insulin-sensitive and insulin-resistant PCOS women because of the reduction in hepatic glucose production.…”
Section: Insulin-sensitizing Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug also reduces appetite in many PCOS women and is thus often [133], but not always [134], associated with more weight loss. Metformin has been shown to be effective in all women with PCOS, even those without insulin resistance and hyperinsulinemia [47, [135][136][137], but tends to be more effective in lean as compared to obese PCOS women [138]. The effects of metformin in PCOS are probably mainly mediated through a reduction in insulin levels, which is observed both in insulin-sensitive and insulin-resistant PCOS women because of the reduction in hepatic glucose production.…”
Section: Insulin-sensitizing Drugsmentioning
confidence: 99%
“…Several studies have demonstrated the therapeutic benefits of one or another TZD on insulin resistance, ovulatory dysfunction and hyperandrogenism in PCOS women [141][142][143][144]. Similar to metformin, TZDs were found to improve hyperandrogenism and ovulation rates even in lean women with PCOS [47,135] and with normal insulin levels [47]. TZDs seem at least as effective as metformin for clinical improvement of PCOS [2,122].…”
Section: Insulin-sensitizing Drugsmentioning
confidence: 99%
“…We chose a 130 -200 nmol/l or 950-1500 ng/ml range as a two-to threefold elevated physiological range indicative of mild insulin resistance. Since that time, several papers have been published showing this two-to threefold elevation in fasting serum insulin levels and in IGF-I levels among PCOS patients (29,30). This study assumes that serum and tubal IGF-I levels are similar.…”
Section: Resultsmentioning
confidence: 97%
“…Several studies have revealed that metfolmin, insulin-sensitizer, treatment for nonobese PCOS improved the metabolic characteristics involving HOMA-R, fasting glucose and insulin levels, area under the curve of insulin response in addition to hyperandrogenism, menstrual irregularities [22][23][24], and pregnancy rate [25].…”
Section: Discussionmentioning
confidence: 99%